A Conceptual Model of the Influence of Mindfulness-Based Interventions on Stress and Quality of Life in Patients With Chronic Conditions. Issue 2 (March 2022) - Prather, Jenifer G.; Baughman, Brandon; Alexandrov, Anne W.; Grimes Stanfill, Ansley
Abstract : Individuals with chronic conditions are susceptible to stress-related health complications. Left unattended, chronic stress exacerbates inflammation, diminishes quality of life (QOL), and increases all-cause mortality. Here, we suggest a theoretical framework promoting the use of mindfulness-based interventions (MBIs) in patients with chronic conditions and a conceptual model of how MBIs may influence stress and QOL.